2020
DOI: 10.1111/jsr.13094
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of virtual agents in a homecare context: Evaluation of excessive daytime sleepiness in apneic patients during interventions by continuous positive airway pressure (CPAP) providers

Abstract: Sleep apnea syndrome treatment relies primarily on continuous positive airway pressure, which requires a homecare follow-up. Excessive daytime sleepiness is a key symptom to be measured during follow-up, and there is a need for more easy-toadminister, ecological and engaging tools to assess it. Virtual agents have shown their How to cite this article: Dupuy L, Micoulaud-Franchi J-A, Philip P. Acceptance of virtual agents in a homecare context: Evaluation of excessive daytime sleepiness in apneic patients durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review included 41 reports, all of which were journal articles 16–23,44–76 . Most of these reports were published within the last 4 years of the review period, a finding that reflects the growth of this area in recent years: 17 reports were published in 2021, 6 reports were published in 2020, 6 reports were published in 2019, and 5 reports were published in 2018.…”
Section: Resultsmentioning
confidence: 99%
“…They also showed that there was no significant difference in the use of the two systems, which therefore did not influence the results on acceptability. Dupuy et al [38] also showed that VA in sleep apnea follow-up is well accepted by both patients and caregivers, regardless of their demographic or clinical characteristics, which is not the case in other studies such as Ref. [39], showing that older and less-educated patients accepted the VA for psychiatric interviews better than younger and welleducated patients.…”
Section: Virtualmentioning
confidence: 91%